Floral Arrangement Collaboration Sharpens Consumer Connection to Locally Grown Flowers - James DelPrince; Wayne Porter; Liz Sadler; Ross Overstreet ([TEST] Journal of Extension, 2021)
Our statewide floral design training program aimed to raise consumer awareness and appreciation of locally grown fresh flowers and to promote extension floral programs through delivery of workshops and demonstrations. Initially, trainees used artificial rather than fresh flowers, necessitating development of a streamlined floral design project plan. Through collaboration with three flower farmers, we developed a floral design prototype. Our growers produced the flowers based on this model and extension provided registration support and media that facilitated locally grown flowers use in workshops. As a result, we connected 47 consumers directly to our producers. Flower growers felt the project was worthwhile and desire future extension partnerships.
Keywords: Flowers; floral design; floral; locally grown; collaboration